Rancang Bangun Aplikasi Pengelolaan Pinjaman Pada Koperasi Simpan Pinjam Abdi Setya Perkasa Surabaya - Helko Prasetiyo; Sulistiowati Sulistiowati; Ignatius Adrian Mastan (Jurnal Sistem Informasi Universitas Dinamika, 2017)
Cooperative Abdi Setya Perkasa which are cooperatives engaged in savings and loans that aim to provide loans to its members in the city of Surabaya. Business processes that occur at this time, the cooperative is still doing records and bookkeeping that makes stacking books and the search data is very old and has not also occur due to missing data book can not be found. Based on the above, the loan management application built which aims to address this data against loss and long to look. The method used to design this loan management application is Waterfall Model. Application management throughout the data shown is borrowing and repayment. The trial results of these applications can display information related to the borrowing member data, data members who pay according to the selected period, as well as proof of payment and the loan is printed and stored in the application management of loans to cooperatives abdi setya perkasa of Surabaya.